Characterization of optical fiber imaging bundles for swept-source optical coherence tomography - Ford, Helen D.; Tatam, Ralph P. (Osa Optical Society of America, 2011)
Fiber imaging bundles have been investigated for use in endoscopic optical coherence tomography (OCT) systems, to obviate the requirement for scanning components within the endoscope probe section. Images have been acquired using several optical configurations, two of which are common path in design. Configurations have been selected as having potential for miniaturization and inclusion in endoscopic-type systems, since the advantages of employing imaging bundles are most clearly seen in this type of system. The various types of bundle available are described, and the properties of the leached bundles used here are discussed in detail, with reference to their effect upon the performance of OCT systems. Images are displayed from measurements made on a range of samples.